PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA KELAS V SD NEGERI 101404 AEK KAHOMBU - Pratiwi, Lili; Siregar, Royhanun; Batubara, Sahiddin; Royi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to determine the effect of using the Discovery Learning learning model on the learning outcomes of class V students at SD Negeri 101404 Aek Kahombu. This research uses a type of experiment with quantitative methods with a one group pretest posttest design. There are two variables in this research, namely the dependent variable, namely the Discovery Learning learning model (X) and the independent variable learning outcomes (Y). The population in this study was class V of SD Negeri 101404 Aek Kahombu, totaling 27 people. The sampling technique is a saturated sampling technique (census) so that the entire population is used as a sample. Before implementing the Discovery Learning learning model, researchers conducted an initial test on students to determine students' abilities, namely the pretest, after that a final test was carried out after applying the learning model, namely the posttest. The average value of learning outcomes obtained at the beginning of the test was 53.74, while the average value of learning outcomes obtained in the final test was 76.11. After the pretest and posttest results have been analyzed to determine whether the proposed hypothesis is accepted or rejected, a t-test is carried out and it is found that the ttable value is 1.71. Frequency (db) is 27-1 =26, at a significance level of 0.05%, tcount is 4.39. Therefore, tcount = 4.39 > ttable = 1.71, significance level 0.05, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which means there is a significant influence after using the Discovery Learning learning model on student learning outcomes.